Gallium oxide impregnated on porous clay heterostructures material for selective catalytic reduction of nitrogen oxide with C3H6. Issue 4 (August 2020) - Kashif, Muhammad; Halepoto, Adeel; Memon, Asadullah; Su, Yaxin; Abduallah, Montaser; Soomro, M.Yakoob
Graphical Abstract: Highlights: The effect of gallium content on PCH support for SCR activity was proposed. 90 % NO conversion by C3 H6 over 24 wt% Ga-PCH catalyst at 350 °C. Well dispersion of Ga in PCH support is achieved via high NO conversion. Gallium loading increases lewis acid site and decreases Bronsted acidic site. Strong stability of Ga-PCH catalyst for NO and better resistance to H2 O and SO2 . Abstract: The porous clay heterostructures (PCHs) were used as a carrier for gallium oxide-based catalyst to convert the nitrogen oxide (NO) to N2 with C3 H6 . The ICP, N2 physisorption, XRD, SEM, XPS, UV-vis and Py-FTIR tests were applied to study the physicochemical properties and the selective catalytic reduction of NO was evaluated in a fixed-bed reactor by C3 H6 . The catalysts with different Ga loading, i.e., 7, 13, 24 and 32 wt% were tested and the best catalytic activity was achieved at 24 wt% Ga-PCH, which exhibits 90% NO x conversion at 350 °C, strong thermal stability and better resistance to H2 O and SO2 . Further, the NO x conversion test demonstrated that adding a small concentration of gallium oxide on porous clay support improves the catalytic efficiency by increasing the acidic concentration and amorphous formation that is beneficial for the conversion of nitrogen oxide (NO) at low temperatures. Meanwhile, the increase of gallium content might be a reason for the agglomeration of Ga2 O3 molecules and blockage of Porous Clay Heterostructures (PCHs) support pores.